Sistem Informasi Paket Haji dan Umroh Pada Al-Faraby Tour And Travel Berbasis Web - Aldi, muhammad wahyu; Sadali, Muhamad; Ahmadi, Hamzan (Fakultas Teknik Universitas Hamzanwadi, 2023)
In carrying out its business activities there are several obstacles faced by PT. Al-Faraby Tour and Travel namely the difficulty for prospective pilgrims to get information related to Hajj and Umrah pilgrimage activities, the difficulty in the registration process because they have to come to the company/office first, and the company is difficult to promote its institution so that it is known by prospective pilgrims more broadly. The purpose of this research is to analyze and design a website-based tour and travel information system for Hajj and Umrah pilgrimages at PT. Al-Faraby tour and travel. The methodology used in the development of this system is the iteration methodology. The results of this study are a website-based information system using PHP and MySQL which is able to overcome existing problems and improve the quality of service to pilgrims in registering Hajj and Umrah. Keywords: Information system, web-based tour & travel.